Social support with anxiety of pregnant mothers in trimester iii facing labor in the time of the covid-19 pandemic in 2022 - Putri, Sartika Dwi Yolanda; Handayani, Sri (Universitas Aisyah Pringsewu, 2022)
Pregnant women have the most intense anxiety among vulnerable and high-risk groups during the COVID-19 pandemic. Increased stress hormone levels limit cervical dilatation, resulting in protracted labor due to excessive worry. One of the reasons of Indonesia's high maternal death rate is prolonged labor. This research sought to identify the variables that impact the anxiety of third-trimester pregnant women at the Community Health Center of Kasihan I during the COVID-19 pandemic in 2022. The study strategy used was a cross-sectional survey approach. The sampling strategy used was purposeful sampling, and the sample size was 74 respondents. Using multiple logistic regression, univariate, bivariate, and multivariate data analyses were conducted. The findings demonstrated a correlation between social support and the anxiety of third-trimester pregnant women at the Community Health Center of Kasihan I in 2022 who were anticipating delivery. This research concludes that there is a correlation between the variable of social support and the anxiety of third-trimester pregnant women. Abstrak: Kecemasan yang dirasakan paling akut pada populasi rentan dan berisiko tinggi dimasa pandemi COVID-19 yaitu pada ibu hamil. Kecemasan yang berlebihan menyebabkan kadar hormon stres dalam tubuh meningkat dan menghambat dilatasi serviks, mengakibatkan persalinan lama. Persalinan lama merupakan salah satu penyebab tingginya angka kematian Ibu di Indonesia. Penelitian ini bertujuan untuk mengetahui faktor-faktor yang mempengaruhi kecemasan ibu hamil trimester III dalam menghadapi persalinan di masa pandemi COVID-19 di Puskesmas Kasihan I tahun 2022. Desain penelitian yang digunakan adalah Cross-Sectional dengan metode survey analitik. Pengambilan sampel dengan teknik purposive sampling, sampel berjumlah 74 responden. Data dianalisis secara univariat, bivariat dan multivariat menggunakan regresi logistik berganda. Hasil penelitian terdapat hubungan antara dukungan sosial dengan kecemasan ibu hamil Trimester III dalam menghadapi persalinan di Puskesmas Kasihan I Tahun 2022. Simpulan penelitian ini variabel dukungan sosial dengan kecemasan ibu hamil trimester III.